Reviews of strategic management research - Ethiraj, Sendil K.; Gambardella, Alfonso; Helfat, Constance E. (Strategic Management Journal, 2017)
SMJ welcomes high‐quality reviews of strategic management research that not only synthesize existing research, but also seek to stimulate new research. As the field of strategic management has matured, many new research streams and perspectives have emerged. Reviews contribute to greater shared understanding and can promote cross‐fertilization across different streams of research . Copyright © 2016 John Wiley & Sons, Ltd.